Strong, Bold, and Kind: Self-Control and Cooperation in Social Dilemmas - Martin G. Kocher; Peter Martinsson; Kristian Ove R. Myrseth; Conny Wollbrant (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We develop a model relating self-control, risk preferences and conflict identification to cooperation patterns in social dilemmas. We subject our model to data from an experimental public goods game and a risk experiment, and we measure conflict identification and self-control. As predicted, we find a robust association between self-control and higher levels of cooperation, and the association is weaker for more risk-averse individuals. Free riders differ from other contributor types only in their tendency not to have identified a self-control conflict in the first place. Our model accounts for the data at least as well as do other models.
urn:nbn:de:bvb:19-epub-12706-5
Keywords: C91; D03; H40; 330; self-control; cooperation; public good; risk; experiment; Persönlichkeitspsychologie; Risikopräferenz; Öffentliche Güter; Spieltheorie; Test